A pipeline for rapid, high-throughput imaging and quantitative analysis of human intestinal organoids - Faith M. Sawyer; Fabio Stossi; Erika Nachman; Robert A. Britton; Michael J. Bolt; Michael A. Mancini; Mary K. Estes; Sarah E. Blutt (PLoS ONE, 2025)
Human intestinal organoids (HIOs) are a model system for studying human intestinal epithelium. Utilizing HIOs for high-throughput studies remains inefficient, as analyzing their cellular composition and responses to varying experimental conditions requires extensive time and labor. We describe a 96-well plate-based automated pipeline for rapidly imaging and quantifying fluorescent labeling in HIOs using a high-throughput confocal microscope and image analysis software. The pipeline was leveraged to quantify varying levels of cell proliferation among donor HIO lines in response to microbial products. Cytoplasmic fluorescence via antibody labeling was also quantified with the pipeline, enabling measurement of the prevalence of specific cell types in HIOs. This platform offers a novel approach to efficiently and rapidly image and quantify fluorescent staining and immunolabeling in HIOs and has many potential applications, including drug screening, toxicity testing, intestinal barrier integrity and transport studies, microbiome and host-pathogen interaction studies, and lineage tracking.